Pleomorphic sarcoma of the eye: a brief literature review and a clinical case - A. Yu. Shamanova; D. D. Voropaev (Российский офтальмологический журнал, 2023)
Pleomorphic sarcomas (PS) are a heterogeneous group of poorly differentiated malignant neoplasms of mesenchymal origin affecting various organs and tissues, which account for 5–7% of all malignant soft tissue tumors. PS most often affects the soft tissues of the extremities, while being extremely rare in the orbital region and the eyeball. The final diagnosis is given after a histological and immunohistochemical (IHC) test of PS supplemented by a cytogenetic test in some cases. The differential diagnosis is based on histogenetic types determined. It should be noted that clinical, instrumental or morphological differential diagnosis between PS of the eye and melanoma is sometimes extremely difficult. The paper presents a case of eyeball PS with an invasion into the orbit, providing a detailed description of the clinical signs of disease, the results of macroscopic, histological and IHC tests of the surgical material, and a review of the literature discussing this pathology. Given the rarity of PS of the eye, the description of the clinical case may be of interest to ophthalmologists and oncomorphologists.